The prevalence of non-classic adrenal hyperplasia among Turkish women with hyperandrogenism - Unluhizarci, Kursad; Kula, Mustafa; Dundar, Munis; Tanriverdi, Fatih; Israel, Shoshana; Colak, Ramis; Kelestimur, Fahrettin (Taylor & Francis Ltd, 2010)
The prevalence of non-classic adrenal hyperplasia (NCAH) among Turkish women with hirsutism has not been established so far. Thus, we aimed to evaluate the prevalence of 21-hydroxylase (21-OH) deficiency by ACTH stimulation test among hirsute women. The study population consisted of 285 premenopousal women, aged 16-46 years (mean: 23.2 +/- 0.3). All were hirsute and hyperandrogenic. Androgen secreting tumors of the ovaries and the adrenal glands were excluded as well as thyroid dysfunction and hyperprolactinemia. All the patients were evaluated by 0.25 mg (i.v.) ACTH stimulation test and 17-OHP responses were obtained at 30 and 60 min. The diagnosis of NCAH due to 21-OH deficiency was considered in patients with the poststimulation 17-OHP level exceed 10 ng/ml. Six (2.1%) of the patients had NCAH due to 21-OH deficiency confirmed by genotyping. The rest of the patients were polycystic ovary syndrome (n = 166, 58.2%) and idiopathic hyperandrogenemia (n = 113, 39.7%). There were no patients with idiopathic hirsutism because patients with normal serum androgen levels were excluded. This first and most extensive national study investigating NCAH prevalence among Turkish population showed that NCAH is not prevalent in this population.
Keywords: Adrenal hyperplasia; hirsutism; polycystic ovary syndrome